Collaboration risk in public networks – specificity, sources and management - Sienkiewicz-Małyjurek, Katarzyna (Wybrane aspekty zarządzania procesami, projektami i ryzykiem w przedsiębiorstwach, 2020)
Collaboration in public networks is nowadays an important and popular tool for the implementation of public services. However, it is associated with many problems arising both from the organization of joint operations and relationships between individual organisations. Emerging collaboration risk is research area where is a lack of theoretical and empirical analysis. Therefore, the purpose of this article is to recognise the specifics and sources of this risk, as well as to analyze its factors on the example of public safety networks and to clarify the role of collaboration risk management. Achieving this goal is based on a critical literature review and the results of structured interviews. As a result, collaboration risk in public networks is characterized and a framework process for managing this risk is proposed.